SPERMATOGENESIS IN Lithobates palmipes(Spix, 1824) IN A FRAGMENT OF NORTHEASTERN ATLANTIC FOREST: espermatogêneses em Lithobatespalmipes(Spix, 1824) em um fragmento de mata atlântica nordestina - Vanessa Alexandre Lourenço; Caio Ian Delfino Oliveira; Marcela Meira Ramos Abrantes; Márcio Frazão Chaves; Stephenson Hallison Formiga Abrantes; Artur da Nóbrega Carreiro (Revista de Ciências da Saúde Nova Esperança, 2025)
Lithobates palmipes(Spix, 1824) is a species of the Ranidae family, mainly associated with lowland tropical rainforests, widely distributed in the Amazon, but also occurring in a disjointed manner in northeastern Brazil, in the Atlantic Forest. Amphibians, in general, have reproductive cycles that can be influenced by climatic factors such as temperature, humidity, and precipitation. This study investigated the histological aspects of the testes of Lithobates palmipes (Spix, 1824) to understand its reproductive cycle and the species’ responses to environmental variations. The species analyzed has a continuous gametogenic cycle, which allows sperm production throughout the year, without depending on rainy or dry seasons. The research was conducted using testicle samples from individuals collected between September 2011 and June 2012 in a fragment of the Atlantic Forest in Mata do Buraquinho, Paraíba. Histological analyses revealed that the testes of Lithobates palmipes (Spix, 1824) exhibit cystic spermatogenesis, with germ cells organized in locules associated with Sertoli cells. During the study period, different stages of spermatogenesis were identified, with a predominance of spermatogonia in some months and the presence of spermatocytes and spermatids in others. These findings indicate that the species maintains continuous reproduction, regardless of seasonal variations in rainfall, which can be explained by the presence of permanent water bodies in the study area. The study reinforces the importance of histological analysis for understanding the reproductive biology of tropical anurans and its relevance for conservation strategies for species inhabiting environments impacted by urbanization. In addition, these results may contribute to environmental management and the protection of species that depend on fragile ecosystems.